Basic of controller design : Theory and applications - Jamaludin, Zamberi; Abdullah, Lokman; Rafan, Nur Aidawaty (Penerbit UTeM Press, 2025)
Rapid advancement in technology has enabling applications of new complex processes and machineries with greater efficiency and productivity. At the heart of these various technological break-through is the ability of the systems to function in the best possible manner with the least errors deemed possible. For these mechatronic systems, well designed motion controller is essential. Control system theory and design are fundamental knowledge in engineering education and highly important to those practicing in the field of robotics and automation. Mastering the control theory and the tools necessary to realise a good controller design is essential for any mechatronics system designer and engineer. However, this can be of great challenge to many aspiring mechatronics engineers. With so many advanced control theory books and references in the market, the choice can be a challenge in itself. An easy-to-follow step-by-step approach to a complete controller design with minimal understanding on the often-complicated control theory would be an attractive option to many in the field.